The Analysis Of Algorithms And Models For Development Of The Adaptive Training Systems - Sevinov J.U., Nashvandova G.M. (International Journal of Advanced Science and Technology, 2020)
This article is devoted to the analysis of models and methods of adaptation and also existing covers for development of the adaptive training systems. The analysis of the problems connected with training of students in technical universities is carried out.